Ethnic Conflicts in Southeast Asia (ISEAS, 2005)
Destabilizing and sometimes changing trajectories of ethnic conflicts have continued to challenge nation-states worldwide. Southeast Asia is no exception: socio-economic and political fault-lines , and tremendous ethnic diversity coupled with uneven development and globalization, have seen resurgence of old conflicts or new ones.